2015
DOI: 10.1002/jaba.236
|View full text |Cite
|
Sign up to set email alerts
|

Delineating subtypes of self‐injurious behavior maintained by automatic reinforcement

Abstract: Self-injurious behavior (SIB) is maintained by automatic reinforcement in roughly 25% of cases. Automatically reinforced SIB typically has been considered a single functional category, and is less understood than socially reinforced SIB. Subtyping automatically reinforced SIB into functional categories has the potential to guide the development of more targeted interventions and increase our understanding of its biological underpinnings. The current study involved an analysis of 39 individuals with automatical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
157
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(171 citation statements)
references
References 86 publications
8
157
6
Order By: Relevance
“…Studies examining functional analysis outcomes by Iwata et al [65] and Hagopian et al [66] reporting on 154 and 176 consecutively encountered cases, respectively found the relative prevalence of functional classes of problem behavior to be comparable to that reported in the literature. Larger scale studies on functional communication training (n=21;n=58 [66,67]); noncontingent reinforcement ( [68],n=27); automatically reinforced SIB [48,49] produced findings comparable that reported across smaller scale studies in body of literature as a whole.…”
Section: Sib Types Features and Sub-types Main Referencessupporting
confidence: 63%
See 1 more Smart Citation
“…Studies examining functional analysis outcomes by Iwata et al [65] and Hagopian et al [66] reporting on 154 and 176 consecutively encountered cases, respectively found the relative prevalence of functional classes of problem behavior to be comparable to that reported in the literature. Larger scale studies on functional communication training (n=21;n=58 [66,67]); noncontingent reinforcement ( [68],n=27); automatically reinforced SIB [48,49] produced findings comparable that reported across smaller scale studies in body of literature as a whole.…”
Section: Sib Types Features and Sub-types Main Referencessupporting
confidence: 63%
“…Recent research has recently delineated subtypes of ASIB [48,49], with clear characteristics related to environmental and biological factors (e.g., higher rates of SIB in conditions with minimal external stimulation in Subtype-1; scarce variability of SIB in all environmental conditions in Subtype-2; and SIB higher when self-restraint is not allowed in Subtype-3). Subtype 1 has positive responsive to treatment (as Socially maintained SIB), whilst Subtype 2 is the most severe and treatment resistant type of SIB.…”
Section: Acta Psychopathologica Issn 2469-6676mentioning
confidence: 99%
“… Hagopian, Rooker, and Zarcone (2015) evaluated a model for subtyping automatically reinforced self-injurious behavior (SIB) based on its sensitivity to changes in functional analysis conditions and the presence of self-restraint. The current study tested the generality of the model by applying it to all datasets of automatically reinforced SIB published from 1982 to 2015.…”
mentioning
confidence: 99%
“…Although there is general consensus regarding the indicators of SIB maintained by automatic reinforcement, our understanding of automatically reinforced SIB is quite limited (LeBlanc, Patel, & Carr, 2000; Vollmer, 1994). Hagopian, Rooker, and Zarcone (2015) proposed and conducted a preliminary evaluation of a model for subtyping automatically reinforced SIB with 39 hospitalized individuals. They based three proposed subtypes on distinct patterns of responding during the functional analysis (FA) and the presence or absence of self-restraint.…”
mentioning
confidence: 99%
“…In addition, we applied the TIRF to compare two groups with SIB known to be differentially resistant to treatment. SIB maintained by automatic reinforcement has been shown to be more resistant to behavioral treatment than SIB maintained social variables (Hagopian, Rooker, & Zarcone, 2015). However, differences between these groups have not been quantified in terms of all aspects of treatment complexity, including the use of medications, staffing, and crisis management resources.…”
mentioning
confidence: 99%